Study of bioactive comp ounds from plants of Rosmarinus officinalis L. with antioxidant activity - Romano, Catalina S. (2006)
It was demonstrated that plant extracts shows similar activities than commercial compounds (ascorbic acid, vitamin E, BHA and BHT) and exhibited positive interactions in combination with them. These results are fundamental for their potential industrial application.